PENGGUNAAN JARGON OLEH KOMUNITAS CHATTING WHATSAPP GRUP - Ayu Wulandari (Universitas Tidar, 2016)
This research has a purpose to describe the use of jargon contained on WhatsApp chat community. The type of this research is descriptive qualitative. The results show that the use of jargon by WhatsApp chat community among students of Applied Linguistics S2 class A of Yogyakarta State University in the academic year of 2013/2014 includes the use of language, form, and function jargon. Overall jargon found in this research were 54 jargons, which consists of 17 jargon in Indonesian, 20 jargon in English, 4 jargon in a foreign language, and 13 jargon in abbreviated form. The findings of this jargon, at least can make a new vocabulary and given its own color in the development of language variation.Kata kunci: jargon, chatting, whatsapp